2020
DOI: 10.3390/v12101164
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon-Based Detection and Sequencing of SARS-CoV-2 in Nasopharyngeal Swabs from Patients With COVID-19 and Identification of Deletions in the Viral Genome That Encode Proteins Involved in Interferon Antagonism

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of coronavirus disease 2019 (COVID-19). Sequencing the viral genome as the outbreak progresses is important, particularly in the identification of emerging isolates with different pathogenic potential and to identify whether nucleotide changes in the genome will impair clinical diagnostic tools such as real-time PCR assays. Although single nucleotide polymorphisms and point mutations occur during the replication of coronaviruse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 27 publications
(27 reference statements)
0
48
0
Order By: Relevance
“…In particular, metagenomic sequencing allows the identification of the normal microbiome of patients, while amplicon-based sequencing allows the amplification and the subsequent sequencing of SARS-CoV-2 viral RNA. Together, amplicon-based sequencing and metagenomic sequencing are able to correctly diagnose COVID-19 infection, thus also identifying secondary infections due to other pathogens aggravating the health status of patients ( 109 ).…”
Section: Alternative Methods For the Effective Diagnosis Of Covid-mentioning
confidence: 99%
“…In particular, metagenomic sequencing allows the identification of the normal microbiome of patients, while amplicon-based sequencing allows the amplification and the subsequent sequencing of SARS-CoV-2 viral RNA. Together, amplicon-based sequencing and metagenomic sequencing are able to correctly diagnose COVID-19 infection, thus also identifying secondary infections due to other pathogens aggravating the health status of patients ( 109 ).…”
Section: Alternative Methods For the Effective Diagnosis Of Covid-mentioning
confidence: 99%
“…SARS-CoV-2 infections can be established by multiple virus genotypes within the same person,7 and together with new rounds of virus replication, provide the raw material for natural selection. The extent of genetic diversity in a viral population is critical to natural selection for growth advantages such as better binding to the receptor, faster replication, and more effective suppression or avoidance of the host immune response.…”
mentioning
confidence: 99%
“…Despite of the larger number of mismatches from R10, the consensus sequence resulted in the same variants detected as from R9. Previous attempts to sequence the SARS-CoV-2 genome have provided accurate results for new variants discovery using rapid workflows based on the ARTIC protocol (Chan et al 2020 ; Li et al 2020 ; Moore et al 2020 ). Other studies also showed amplicon sequencing using ONT flongle flow cells (Chan et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%